2016
DOI: 10.1002/ajmg.a.38029
|View full text |Cite
|
Sign up to set email alerts
|

Camptodactyly and the 22q11.2 deletion syndrome

Abstract: We describe a 5-day-old male with minor facial anomalies, a congenital laryngeal web, severe laryngomalacia, and prominent fixed flexion of the proximal interphalangeal joints of digits 2 through 5 bilaterally. A whole genome SNP microarray analysis identified a 2.55 Mb interstitial deletion of 22q11.21, typical of that seen in the DiGeorge and Velocardiofacial syndromes. A review of the literature identifies 10 other cases with camptodactyly. Camptodactyly appears to be an associated but rarely reported anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The pathogenesis of camptodactyly is not clear [ 7 , 8 , 9 ]. Although some cases occur sporadically, it has been proven to show an autosomal inheritance pattern [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The pathogenesis of camptodactyly is not clear [ 7 , 8 , 9 ]. Although some cases occur sporadically, it has been proven to show an autosomal inheritance pattern [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of camptodactyly is not clear [ 7 , 8 , 9 ]. Although some cases occur sporadically, it has been proven to show an autosomal inheritance pattern [ 7 , 8 ]. Malik et al [ 7 ] described a case of a German family with thirteen camptodactyly cases in four generations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Couser et al have shown that there is a link between the appearance of camptodactyly and deletion of the 22q11.21 chromosome. Later on, ten cases of children with 22q11.21 deletion presenting with camptodactyly were described in the literature 9 .…”
Section: Classification and Diagnosismentioning
confidence: 99%